Humor of the Leader: A Source of Creativity of Employees Through Psychological Empowerment or Unethical Behavior Through Perceived Power? The Role of Self-Deprecating Behavior - Ali, Hassan; Mahmood, Asif; Ahmad, Ayyaz; Ikram, Amir (Frontiers in Psychology, 2021)
Although we use humor in our daily communication, still there needs to cognize its effects on employees’ attitude and behavior. Based on Benign Violation Theory, the study proposes that a leader’s humor conveys social information about counter norms. Benign Violation Theory has been amalgamated with Social Information Processing Theory to develop hypotheses assuming the consequences of leader’s humor on employees’ attitude and behavior. This study hypothesizes that even though leader’s humor is linked positively with employee creativity via leader-member exchange and psychological empowerment in sequence (blessing path), it may also send information to the employees about the acceptability of norm violation. This perception ultimately leads to power perception and, causes unethical behavior in the series (curse path). Moreover, this study also postulates that leader’s self-deprecating humor moderates these indirect effects by enhancing the blessing and reducing the curse, which emerged from leader’s humor. Quantitative data of 630 software engineers from software houses based in Pakistan provided support to test the hypotheses. The results demonstrate that leader’s humor is a double-edge sword that enhances blessing (creativity) as well as curse (employee unethical behavior), whereas leader’s self-deprecating humor augments the blessing and throttles back the curse. Theoretical and managerial implications have also been discussed.